Customary Deliberation and Local Democracy: The Strategic Role of the Tolaki Traditional Assembly in Sustaining Cultural Governance in Southeast Sulawesi, Indonesia - Ramadhan Tosepu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Customary deliberation is an essential component of the social and cultural life of the Tolaki people in Southeast Sulawesi. This tradition has been passed down through generations and serves as a primary means for making collective decisions, resolving conflicts, and maintaining harmony among community members. Customary deliberation not only reflects the Tolaki people's approach to preserving social order but also demonstrates how cultural values and principles of local democracy are embodied in inclusive deliberative processes. This article explores the strategic role of customary deliberation in strengthening the social structure of the Tolaki community, using a case study of the 5th Central Customary Assembly organized by the Central Executive Board of Organization for Tolakinese Culture and Customs in May 2025. Through a qualitative and document-based analytical approach, the article examines how customary deliberation forums function as mechanisms for preserving cultural identity while simultaneously serving as platforms for legitimate and socially accepted leadership regeneration. The deliberative process reveals how customary communities are able to respond to contemporary challenges without losing their cultural essence. Therefore, customary deliberation is not merely a tradition but also a vital part of a vibrant and participatory democratic practice in the context of local governance in contemporary Indonesia. Keywords: Customary Deliberation; Tolaki Customary Institution; Local Democracy; Tolaki; Southeast Sulawesi